HIGHER EDUCATION OF UKRAINE AND THE BOLOGNA PROCESS (Pedagogy of Higher and Secondary Education, 2007)
In article the question of occurrence of Ukraine in Bolon’s process, the substantive provisions showed to countries-participants of Boloris process, and also some problems accompanying this process is considered.